The genome affair - Sayeedi, Vicar (Vicar Sayeedi, 2021)
"Singularity is the point at which Human Intelligence and Artificial Intelligence converge. Cognitive and computer scientists believe Deep Learning Neural Networks will achieve singularity in 2040. But what if sigularity were achievable now? What if Artificially Intelligent sentient beings exceeded singularity today? What would the implications be for our world? This is the story of Genome."-- from back cover